Crédito rural e produto agropecuário: evidências empíricas para o Brasil - Nascimento, Daniel Henrique (2017)
The objective of this study is to evaluate the relationship between the gross value of agricultural production and the rural credit concessions in Brazil for the quarterly period from 2002 to 2015. We consider in the study the exogenous variables of compulsory directives and deposits of demand deposits and Savings. Using the structure of a VAR model with cointegration, the results indicate the existence of a long-term relationship between the loans for the agricultural sector and its product. The estimated average long-term elasticity for the period resulted in 0.44. Regarding the directives and collections, there is no evidence of their effectiveness in the rural credit disbursements or the agricultural product.